Analysis of the correlation between non-alcoholic fatty liver disease and the risk of colorectal neoplasms - Ye, Shujun; Liu, Yang; Zhang, Te; Feng, Huijin; Liu, Yanqing; Ma, Lianjun (Frontiers in Pharmacology, 2022)
This study aims at assessing the potential association between non-alcoholic fatty liver disease (NAFLD) and colorectal neoplasms (CRN). PubMed, Cochrane Library, and Embase were searched for cohort studies. 14 cohort studies with a total population of 38,761,773 were included for meta-analysis after selection. The results showed that NAFLD is related to an increased risk of CRN (OR = 1.23; 95% CI: 1.14–1.32; I2 = 70.7%, P<0.001). In the subgroup analysis, NAFLD were found to be the independent risk factor of colorectal adenoma (CRA) (OR=1.29; 95%CI=1.15-1.45; I2=66.4%) and colorectal cancer (CRC) (OR=1.13; 95%CI=1.12-1.15; I2=69.4%). There is no close correlation between smoking status of NAFLD patients and CRN. Interestingly, bioinformatics analysis revealed that there were overlap of dysregulated gene sets among NAFLD, CRC, and two recently identified regulated cell death types, ferroptosis and cuproptosis, respectively. Our meta- and bioinformatics analysis shows that NAFLD increases the risk of CRN. Ferroptosis and cuproptosis may be the critical links between NAFLD and CRN, respectively. These findings here support that NAFLD is necessary to be considered as an emerging risk factor for CRN.